Disentangling the Age, Period, and Cohort Effects using a Modeling Approach - France Portrait; Rob Alessie; Dorly Deeg (Tinbergen Institute, 2002)
Disentangling age, period, and cohort effects in explaining health trends is crucial to assess future prevalences of health disorders. The identification problem – age, period, and cohort effects are perfectly linearly related – is tackled by modeling cohort and period effects using lifetime macro-indicators. This approach – innovative in analyses on health trends – handles theidentification problem and explains mechanisms underlying cohort and period effects. The modeling approach is compared with graphical and two-factors methods. The methods are applied on Dutch trends in functional limitations using data from the Longitudinal Aging Study Amsterdam. We argue that the modeling approach is a highly appropriate alternative. We find that theprevalence of functional limitations increases in the nineteen-nineties due to adverse cohort and period effects. Cohort effects are explained by hygienic and socio-economic conditions during childhood and period effects by restrictions in availability of health care services.
Keywords: I1; C4; 330; Age-Period-Cohort Analysis; Trends in Functional Limitations; Aging; Alte Menschen; Krankheit; Niederlande; Ökonometrisches Modell